Nutrition-induced macular-degeneration-like photoreceptor damage in jumping spider eyes. (May 2023) - Rathore, Shubham; Goté, John T.; Brafford, Miranda; Morehouse, Nathan I.; Buschbeck, Elke K.; Stowasser, Annette
Highlights: Jumping spider retinal health is compromised by nutrient deprivation in development. Optical and TEM data clearly indicate signs of photoreceptor degeneration. Photoreceptor degeneration is most prominent in the high-density photoreceptor region. Jumping spiders present a compelling model to investigate retinal and neuronal health. Abstract: Age-related macular degeneration (AMD) is a leading cause of vision loss in humans. Despite its prevalence and medical significance, many aspects of AMD remain elusive and treatment options are limited. Here, we present data that suggest jumping spiders offer a unique opportunity for understanding the fundamentals underlying retinal degeneration, thereby shedding light on a process that impacts millions of people globally. Using a micro-ophthalmoscope and histological evidence, we demonstrate that significant photoreceptor damage can occur during development in the image-forming anterior lateral eyes of the jumping spider Phidippus audax . Furthermore, we find that this photoreceptor degeneration is exacerbated by inadequate nutrition and is most prevalent in the high-density region of the retina, like AMD in humans. This suggests that similar to those in vertebrates, the retinas in P. audax are challenged to meet high-energy cellular demands.